Peningkatan Keterampilan Membaca Permulaan Siswa Melalui Media Buku Cerita Bergambar Kelas II di Sekolah Dasar Islam Nurul Huda Jatipulo : Penelitian - Maulitha Rahma; Oktian Fajar Nugroho (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This research is motivated by the low learning outcomes of Indonesian language of second-grade students of Nurul Huda Islamic Elementary School Jatipulo due to learning that is still centered on books so that students are less active. This study aims to improve early reading skills through the use of picture story books. The research subjects were 14 students, consisting of 6 female students and 8 male students. The method used was Classroom Action Research (CAR) with the stages of planning, implementation, observation, and reflection in each cycle. Data analysis was carried out descriptively on test results and observation sheets. The results showed an increase in student activity and learning outcomes, marked by learning completeness of 71% in cycle I and increased to 86% in cycle II. The percentage of teacher observations increased from 75% to 87%, while student observations increased from 76% to 83%. These results indicate that the use of picture story books is effective in improving the early reading skills of second-grade students of Nurul Huda Islamic Elementary School Jatipulo.